The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
DOI: 10.29007/hf15
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review on Cybersecurity Threats to Healthcare Data and Mitigation Strategies

Khanyisile Vilakazi,
Funmi Adebesin

Abstract: The incidence of cyberattacks on healthcare institutions has seen a steady increase over the years, with a massive increase of 42% in 2020. More specifically, INTERPOL reported a substantial increase in ransomware attacks on healthcare institutions at the height of the Covid-19 pandemic. This increase can be attributed to the rise in the adoption of digital technologies, such as the Medical Internet of Things (MIoT), to support healthcare services. The sensitive nature of healthcare data and the volume of data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 45 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…Sardi et al [38] literature review strengthens the themes raised by the previous two literature reviews [34,35] regarding the growing cyber-risk in healthcare. Their analysis identified four key themes: human actions, system failures, internal process breakdowns, and external events.…”
Section: Literature Surveymentioning
confidence: 60%
See 2 more Smart Citations
“…Sardi et al [38] literature review strengthens the themes raised by the previous two literature reviews [34,35] regarding the growing cyber-risk in healthcare. Their analysis identified four key themes: human actions, system failures, internal process breakdowns, and external events.…”
Section: Literature Surveymentioning
confidence: 60%
“…Vilakazi and Adebesin [34] conducted a systematic literature review to explore mitigation strategies for cybersecurity threats targeting healthcare data. The review identified several critical vulnerabilities in healthcare cybersecurity.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Because humans are considered the weakest link, smart healthcare providers must conduct regular training and awareness programs to educate healthcare professionals, patients, and other stakeholders about cyber threats and best security practices through lectures, seminars, and games [139][140] [168]. Smart healthcare users need high-quality education and training programs that include up-to-date information, tips, recommendations, and campaigns that are simple to remember and apply to prevent healthcare user-related cyber-attacks.…”
Section: Security Awareness and Trainingmentioning
confidence: 99%
“…For example, healthcare users are trained on phishing attacks, patient rights, sensitive patient medical data security, SHS or end-user device security, IoMT device and application protection, the risks associated with data breaches and cyberattacks, and best security practices for strong login credentials and network and Wi-Fi security [141]. Training healthcare professionals and patients on best security practices and potential cyber threats in SHSs can help reduce human error, prevent security breaches caused by social engineering attacks, avoid unintended medical data leaks, reduce cybersecurity incidents, and improve patient safety and well-being [168].…”
Section: Security Awareness and Trainingmentioning
confidence: 99%